2021
DOI: 10.1108/lodj-04-2021-0190
|View full text |Cite
|
Sign up to set email alerts
|

Integrating relational systems theory with ethical leadership: how ethical leadership relates to employee turnover intentions

Abstract: PurposeAs ethical leadership has advanced as a construct, the degree to which healthy relational systems explain its effect on employee outcomes has been understudied. With this manuscript we conceptualize and test a model based on a Relational Systems approach to ethical leadership and its relationship with conflict and turnover intentions.Design/methodology/approachTwo studies were conducted to test our hypothesized first- and second-stage moderated mediation model. In Study 1, online surveys were completed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 88 publications
1
8
0
Order By: Relevance
“…Supporting relational systems theory, this study found that at the time of crisis high-quality workplace relational systems act to augment optimistic behavior toward the work environment and predict employee work engagement. Which is in line with the findings of existing research which explained that healthy workplace relational systems strengthen employee bonding with the workplace [ 31 , 131 ].…”
Section: Discussionsupporting
confidence: 91%
“…Supporting relational systems theory, this study found that at the time of crisis high-quality workplace relational systems act to augment optimistic behavior toward the work environment and predict employee work engagement. Which is in line with the findings of existing research which explained that healthy workplace relational systems strengthen employee bonding with the workplace [ 31 , 131 ].…”
Section: Discussionsupporting
confidence: 91%
“…Employee turnover occurs as a voluntary termination of the job contract even if the employee still has an opportunity to remain with the employer (Maertz & Campion, 1998). Although reasons for employee turnover can be varied, such as incompetent salary (McCartney et al, 2022), poor ethical leadership (Marquardt et al, 2022), and co‐worker relationship quality (Qiu et al, 2014), job satisfaction is considered as a strong (Lee et al, 2012; Zhou & He, 2014) and imminent indicator of employee turnover (Choi, 2006). Job satisfaction reflects a positive attitude toward the organization, thus directly influencing employee turnover intentions (Ongori, 2007).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Over time, scholars have attempted to answer two crucial questions related to employee retention: “Why do people leave?” and “Why do people stay?”. The initial attempt was made by Simon and March (1958), who asserted that one's inclination to quit is influenced by both their desire to exercise and how easy one considers their movement to be (Marquardt et al ., 2022). Mitchell et al .…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%